1258 No Laughing Matter - Laughter Induced Syncope (Gelastic Syncope) Mimicking Cataplexy. (27th May 2020) - Belani, Dinesh; Simon, Edwin
Abstract: Introduction: Laughter is a common emotion and may rarely be a manifestation of neurological illnesses. It has been associated with cataplexy as well. Cataplexy is usually triggered by strong emotions. Gelastic syncope is an uncommon phenomenon which may be mistaken for cataplexy. We summarize 3 cases referred to the Sleep Medicine clinic for evaluation for Narcolepsy. Report of Case: 55 yo male comes with 2 episodes of blacking out and falling down relating to episodes of laughter in 3 months. Patient describes loss of consciousness and no episodes of freezing. Reported 15 years of snoring and witnessed apneas along with grinding his teeth while sleeping. Polysomnogram revealed Obstructive Sleep Apnea (OSA) with an AHI of 20. 60 yo male comes with episodes of loss of consciousness over the past 6 months, including sitting in a chair, laughing, urinating, washing dishes while standing, expressing strong emotions (father's funeral), etc. Also reports bugs crawling over his legs when trying to sleep, loud snoring and waking up choking while sleeping. Polysomnogram revealed OSA with an AHI of 20. 43 yo male comes 3 episodes of loss of consciousness, 2 of them related to laughing and the last one related to stretching his arms out. He passes out for 5-10 seconds at a time and a period of 20-30 seconds before passing out where he feels dizzy when he is unable to respond at this time, no post episode confusion. Positive on the Cataplexy Emotional Trigger Questionairre. Reported witnessed apneas, snoring and sleep talking. Polysomnogram revealed OSA, hence the Multiple Sleep Latency Testing ordered was not completed. Conclusion: While the first two episodes point towards Gelastic Syncope based on symptoms, the third did warrant MSLT if there was no OSA on PSG. It is important to recognize gelastic syncope as an entity and differentiate it from cataplexy.